Turkish chatbot app - Tahmilci Ekin Mete; Isiklar Ahmet Can; Kirci Pinar (онлайн, 2022)
Today, e-commerce sites and many sectors use chatbot applications to provide customer service. Chatbots appear in customer service as well as sentiment analysis, marketing and diagnostic applications. Chatbot systems form the infrastructure of voice assistants in new generation operating systems. These voice assistants, which can perform different tasks from setting an alarm to making a hair dresser appointment, have deeply influenced and developed the human-robot relationship. The aim of this project is to examine the performance of the chatbot produced with BoW method, and to reveal the advantages and disadvantages.